Neuronal hyperexcitability in dystrophin-deficient mdx hippocampal neurons: the importance of interleukin-6 and GABAergic regulation - Kimberley A. Stephenson; Qiao Xiao; Michael B. Vaughan; Polly Peters; Claire Denley; Sean O’Meara; Cecelia Sheehan; Mark G. Rae; Dervla O’Malley (Scientific Reports)
Abstract Duchenne Muscular Dystrophy (DMD) is a severe neuromuscular disorder arising from loss of the structural protein, dystrophin. It also often presents with cognitive deficits and susceptibility to epilepsy. Expressed in neurons of the hippocampus, dystrophin plays an important role in synapse formation, specifically the post-synaptic organisation of γ-aminobutyric acid A receptors (GABAARs). This study explored possible interactions between interleukin (IL)-6, which is elevated in DMD, and GABAAR signalling in cultured hippocampal neurons of dystrophic mdx mice. Immunofluorescent imaging revealed altered development of network connectivity that displayed similar characteristics to dystrophin-expressing neurons cultured in elevated levels of IL-6. Mdx neurons dependably exhibited spontaneous oscillations. Calcium (Ca2+) signalling was further modulated by exposure to agonists and antagonists of GABAA and GABABRs. IL-6-evoked Ca2+ responses were enhanced by muscimol, a GABAAR agonist, in wildtype (WT) and mdx neurons, whilst bicuculline, a GABAAR antagonist, only suppressed IL-6-evoked Ca2+activity in WT neurons. The GABABR agonist, baclofen, enhanced IL-6-evoked Ca2+ responses only in mdx neurons. Our findings support dysfunctional GABAergic signalling in hippocampal neurons that lack dystrophin, resulting in aberrant neuronal network excitability. The contribution of elevated levels of IL-6 further impact upon Ca2+ dyshomeostasis in dystrophic neurons and may underpin cognitive changes reported in dystrophinopathies.